Effect of grip strength and grip strengthening exercises on instantaneous bat velocity of collegiate baseball players - Hughes, S. S.; Lyons, B. C.; Mayo, J. J. (The Journal of Strength and Conditioning Research, 2004)
Bat velocity is considered to be an important factor for successful hitting. The relationship between grip strength and bat velocity has not been conclusively established. The purposes of this study were to determine the relationship of grip strength to bat velocity and to ascertain whether the performance of resistance training exercises designed to specifically target the forearms and grip would significantly alter bat velocity. The subjects for this study were 23 male members (mean ± SD, age = 19.7 ± 1.3 years, height = 182.5 ± 5.9 cm, weight = 85.4 ± 15.5 kg, experience = 14.4 ± 1.7 years) of a varsity baseball team at a National Collegiate Athletic Association Division II school. The Jamar hand dynamometer was used to test grip strength, and the SETPRO Rookie was used to measure instantaneous bat velocity at the point of contact with the ball. Subjects were randomly divided into an experimental group and a control group. For 6 weeks, both groups participated in their usual baseball practice sessions, but the experimental group also performed extra forearm and grip strengthening exercises, whereas the control group did not. Pretest and posttest correlations between grip strength and bat velocity revealed no significant relationship between grip strength and bat velocity (pretest r = 0.054, p = 0.807; posttest r = 0.315, p = 0.145). A dependent t-test performed on all subjects revealed that a significant (p = 0.001) increase in bat velocity did occur over the course of the study. A covariate analysis, employing pretest bat velocity as the covariate, revealed no significant difference (p = 0.795) in posttest bat velocity scores between the experimental and control groups. Thus, increases in bat velocity occurred, but the differences were similar for both the experimental and control groups. The findings of this study suggest that grip strength and bat velocity are not significantly related, and that the allocation of time and energy for added training of the forearms in order to improve grip strength for the purpose of increasing bat velocity may not be warranted.